Danton's Death Based on a Play by Georg Büchner - Büchner, Georg (BFI, 2016)
"Danton's Death" is arguably the most dramatic and penetrating study of revolution ever written. Georg Büchner concentrates on that moment in 1794 when the Reign of Terror, already well established, spills over into a total blood-bath. The play, adapted by director Alan Clarke and Stuart Griffiths, both highly imaginative and closely documentary, shows how the great hero of the early phase of the Revolution, Danton, sickened by the excesses of the guillotine, which he helped to create, wants to call a halt. But Robespierre and Saint-Just, the leaders of the extremists, with a ferocious puritanical zeal, spur on "the wild horses of the Revolution". [letterboxd.com]
Keywords: DVD-Video